Establishment of rat allogenic vein replacement model and pathological characteristics of the replaced vessels - Ren, Zhangyong; Cui, Songping; Lyu, Shaocheng; Wang, Jing; Zhou, Lin; Jia, Yanan; He, Qiang; Lang, Ren (Frontiers in Surgery, 2022)
Abstract Background: With the advancement of vascular anastomosis techniques in recent years, radical surgery for tumors combined with venous vascular resection and reconstruction has been widely used. This study intends to establish two different rat vein replacement models, and further analyze the pathological changes of blood vessels after replacement. Methods: Brown-Norway (BN) rats were selected as donors and recipients, randomly divided into control group, cuff group (1-week group, 2-week group, and 4-week group), and suture group (1-week group, 2-week group, and 4-week group), with 6 rats in each group. The perioperative conditions, inner diameter, flow velocity and histopathological changes of the replaced vessels at different time points were analyzed. Results: Both cuff group and suture group can safely establish the rat vein replacement model. From the surgical operation, the operation time and venous cross-clamp time in the cuff group were shorter than those in the suture group (P < 0.05). At 2 and 4 weeks after operation, the diameter of suture group was wider than that of cuff group, and the flow rate was faster (P < 0.05). With prolonged postoperative survival, the wall of the replaced vessels underwent infiltration of CD4 + and CD8 + lymphocytes and high TGF-β1 gene expression. This leads to the proliferation of blood vessels and intimal layer. The results of vascular pathological staining showed that the infiltration degree of CD4 + lymphocytes at 2 weeks after operation and CD8 + lymphocytes at 4 weeks after operation in the suture group was lighter than that in the cuff group (P < 0.05). Meanwhile, TGF-β1 gene content at 4 weeks after operation in suture group was significantly lower than that in cuff group (P < 0.05). Conclusion: Compared with cuff method, suture method is more suitable for the study of long-term pathological changes after vein replacement in rats. The main pathological changes in the long term after venous replacement in syngeneic background may be vascular fibrosis caused by inflammatory cell infiltration.